Accountant Ethics: The Role of Islamic Work Ethic as a Solution - Indra Caniago; Reva Meiliana; Taufik Taufik (Bukhori: Kajian Ekonomi dan Keuangan Islam, 2023)
Purpose: The fraud problem has occurred for a long time, followed by accounting scandals including Enron, Worldcom, Satyam, and Global Crossing. This problem is observed from the problems in accounting ethics. This study reviews the literature on ethical self-regulation in accounting from 1980-2020. The articles referred to are those published in Scopus indexed journals. Various solutions were presented from various articles such as improving regulations and professional ethics, free choice of standards used in accounting methods, perceptions of accountants to ethics education in accountants. All of these suggestions have advantages and disadvantages. This paper offers an Islamic work ethic as a solution to the ethical self-regulation of accountants that has a strong dimension with a backing on the divine aspect. This paper offers an Islamic work ethic as a solution to the ethical self-regulation of accountants that has a strong dimension with a backing on the divine aspect. Method: This paper uses harzing software to compile articles on ethical regulation in accountants from the 1980s to 2020. The articles referred to are those published in Scopus indexed journals. The results of tracing articles found very little data discussing regulations on accounting ethics. After the screening process, only six articles were found to be relevant (Table 1). Table 2 shows that most of the articles are conceptual papers. The rest use survey, qualitative and archival methods. Result: So with various improvement efforts in these various fields, this paper suggests an Islamic work ethic as a solution to the problem of accountant ethics. This ethic can be universally applicable because it involves the individual's relationship with his God. All actions return to intentions that focus on the process, not only on the results. Limitation: The limitation of this article is that it only discusses the aspect of self-regulation. Studies from different aspects will add to the contribution of ethical studies in accounting.